5-Aminolevulinic acid-mediated sonosensitization of rat RG2 glioma cells in vitro - Bilmin, Krzysztof; Kujawska, Tamara; Secomski, Wojciech; Nowicki, Andrzej; Grieb, Paweł (Folia Neuropathologica, 2016)
Sonodynamic therapy (SDT) is a promising technique based on the ability of certain substances, called sonosensitizers, to sensitize cancer cells to non-thermal effects of low-energy ultrasound waves, allowing their destruction. Sonosensitization is thought to induce cell death by direct physical effects such as cavitation and acoustical streaming as well as by complementary chemical reactions generating oxygen free radicals. One of the promising sonosensitizers is 5-aminolevulinic acid (ALA) which upon selective uptake by cancer cells is metabolized and accumulated as protoporphyrin IX. The objective of the study was to describe ALA-mediated sonodynamic effects in vitro on a rat RG2 glioma cell line. Glioma cells, seeded at the bottom of 96-well plates and incubated with ALA (10 µg/ml) for 6 h, were exposed to the sinusoidal US pulses with a resonance frequency of 1 MHz, 1000 µs duration, 0.4 duty-cycle, and average acoustic power varying from 2 W to 6 W. Ultrasound waves were generated by a flat circular piezoelectric transducer with a diameter of 25 mm. Cell viability was determined by MTT assay. Structural cellular changes were visualized with a fluorescence microscope. Signs of cytotoxicity such as a decrease in cell viability, chromatin condensation and apoptosis were found. ALA-mediated SDT evokes cytotoxic effects of low intensity US on rat RG2 glioma cells in vitro . This cell line is indicated for further preclinical assessment of SDT in in vivo conditions.